Natural Products for Managing Landscape and Garden Pests in Florida - Eileen A. Buss; Sydney G. Park Brown (EDIS)
This publication describes “natural” pesticides: alternatives that are usually less toxic to non-target organisms and the environment and that, when used correctly, can be effective substitutes for synthetic products. In this publication, natural substances used for pest management in landscapes and gardens are grouped into oils, plant extracts, insecticidal soaps, mineral insecticides, microbial insecticides, and products that control diseases. Certain products contain combinations of these groups (e.g., soap and oil). This revised 8-page fact sheet was written by Eileen A. Buss and Sydney G. Park Brown, and published by the UF Department of Entomology and Nematology, June 2014.